Polycentric Theology, Mission, and Mission Leadership. (July 2021) - Ross, Kenneth
Though it began with an assumption that there was one universal and normative Christian theology, the modern missionary movement has resulted in the emergence of polycentric theology. As each new centre thinks through the meaning of the faith in contextual terms, it offers a distinctive theology – to the extent that it becomes a question whether any universal theological affirmation can be possible. Meanwhile the theory and practice of mission has been no less radically reshaped by a polycentric vision, with the concept of "mission from the margins" capturing the imagination. A profound openness to others and, ultimately, the deep spiritual discernment that is sensitive to the presence and action of the Spirit of God in our world, is the essential equipment needed for leadership in mission today.